2003
DOI: 10.1118/1.1626990
|View full text |Cite
|
Sign up to set email alerts
|

Summary and recommendations of a National Cancer Institute workshop on issues limiting the clinical use of Monte Carlo dose calculation algorithms for megavoltage external beam radiation therapy

Abstract: Due to the significant interest in Monte Carlo dose calculations for external beam megavoltage radiation therapy from both the research and commercial communities, a workshop was held in October 2001 to assess the status of this computational method with regard to use for clinical treatment planning. The Radiation Research Program of the National Cancer Institute, in conjunction with the Nuclear Data and Analysis Group at the Oak Ridge National Laboratory, gathered a group of experts in clinical radiation ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…A major advantage of MC dose engine over conventional engines is the lower systematic error in dose computation 1. Verification of its dosimetric accuracy provides clinicians with a better understanding of dose in regions of heterogeneity, enabling more accurate treatment in regions which may have previously been complicated by systematic error in delivered dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major advantage of MC dose engine over conventional engines is the lower systematic error in dose computation 1. Verification of its dosimetric accuracy provides clinicians with a better understanding of dose in regions of heterogeneity, enabling more accurate treatment in regions which may have previously been complicated by systematic error in delivered dose.…”
Section: Discussionmentioning
confidence: 99%
“…Fraass et al had reported that a dose error of 5% could lead to a tumor control probability (TCP) change of 10–20% and an even higher change in normal tissue complication probability (NTCP) 1. Noticeable clinical effects of dose errors of 7% have been reported in TG‐65 by Papanikolaou et al2 Reducing the uncertainties in dose calculation will reduce the overall uncertainty in delivered dose to within 5% as recommended by International Commission on Radiation Units and Measurements (ICRU) report 24 3…”
Section: Introductionmentioning
confidence: 99%
“…By calculating the trajectories and interactions of a very large number of photons and electrons, one can accurately model the dose distribution. Recently, several Monte Carlo codes have been devel-oped for radiotherapy treatment planning (Cygler et al 2004;Fraass et al 2003 …”
Section: Advanced Dose Calculationmentioning
confidence: 99%
“…It has been claimed that progress in development of such complex electron treatments has been limited by inaccuracies in electron beam dose calculations 14 . The principle incentive for the present study was the accurate calculation of dose distributions for narrow fields.…”
Section: Introductionmentioning
confidence: 99%